Comparison of the etiological causes in patients under and/or over the age of 65 admitted to the emergency department with non-traumatic chest pain - Yılmaz, Funda; Armağan, Erol; Kaya, Halil; Yüksel, Melih; Çelik, Kamuran; Uygun, Erman; Özkan Yıldız, Havva Özge; Gafuroğulları, Sibel (The European Research Journal, 2021)
Objectives: One of the most common reasons for admission to the emergency department is chest pain. The clinical presentation of chest pain is quite wide. The study aimed to compare the diagnoses of patients under and/or over the age of 65 admitted to the emergency department with non-traumatic chest pain. Methods: A thousand patients admitted to the emergency department with non-traumatic chest pain between 15.10.2014 and 15.07. 2015 were included in the study. Patients were divided into two groups according to age group as < 65 years old and ≥ 65 years old. Age, gender, the type of admission, comorbidities, accompanying symptoms, diagnosis, outcome and hospitalization were recorded. Results: Five hundred eighteen males and 482 females were included in the study. Eight hundred nineteen patients were between the ages of 18 to 64. The most common accompanying symptom was dyspnea in both age groups. Hypertension was the most common concomitant disease in the 18-64 year age group while coronary artery disease was the most common diseasein the 65 and over age group. Conclusions: Non-cardiac chest pain is more common in the young population admitted to the emergency department while life-threatening chest pain is more common in the population over the age of 65.